Clinical‐radiological‐pathological correlation in an unusual case of refractory epilepsy: a two‐year journey of whodunit!. Issue 1 (6th March 2018) - Menon, Deepak; Menon, Ramshekhar N; Kesavadas, Chandrasekharan; Mahadevan, Anita; Radhakrishnan, Ashalatha; Kannoth, Sudheeran; Nair, Pradeep P; Abraham, Mathew; Thomas, Bejoy; Thomas, Sanjeev V
ABSTRACT: New‐onset refractory focal epilepsy poses significant challenges to the clinician in the absence of specific diagnostic biomarkers. Differential diagnoses based on imaging may be expanded by a veritable spectrum of peri‐ictal imaging findings that may mask the underlying substrate. We report a 13‐year‐old girl who presented with refractory focal seizures of left parieto‐occipital origin with cytotoxic gyral oedema noted over the same region on imaging. Despite an initial negative autoantibody profile, the patient was treated with immunosuppression, followed by serial relapses requiring immune‐modulation. Over the next year, her syndrome persisted as focal left posterior cortex epilepsy that necessitated occipital lobectomy, following a relapsing‐remitting radiological profile, consistent with peri‐ictal MRI changes. Histopathology was inconclusive for any definitive substrate. After a period of quiescence, she developed focal motor seizures of right hemispheric origin with progressive encephalopathy, at which point a repeat cerebrospinal fluid anti‐N‐methyl‐D‐aspartate receptor antibody profile returned positive. The patient was managed with steroids and rituximab with a good clinical outcome. We hypothesise that persistent or relapsing‐remitting focal gyral oedema in unexplained refractory focal epilepsy mandates consideration of focal encephalitis secondary to autoimmunity, and late appearance of intrathecal auto‐antibody synthesis correlates with evolution into a more diffuse disease.